Novel and nodulation-regulated microRNAs in soybean roots - Zhu Jian-Kang; Barbazuk W Brad; Sunkar Ramanjulu; Fu Yan; Subramanian Senthil; Yu Oliver (BMC Genomics, 2008)
Abstract Background Small RNAs regulate a number of developmental processes in plants and animals. However, the role of small RNAs in legume-rhizobial symbiosis is largely unexplored. Symbiosis between legumes (e.g. soybean) and rhizobia bacteria (e.g. Bradyrhizobium japonicum) results in root nodules where the majority of biological nitrogen fixation occurs. We sought to identify microRNAs (miRNAs) regulated during soybean-B. japonicum symbiosis. Results We sequenced ~350000 small RNAs from soybean roots inoculated with B. japonicum and identified conserved miRNAs based on similarity to miRNAs known in other plant species and new miRNAs based on potential hairpin-forming precursors within soybean EST and shotgun genomic sequences. These bioinformatics analyses identified 55 families of miRNAs of which 35 were novel. A subset of these miRNAs were validated by Northern analysis and miRNAs differentially responding to B. japonicum inoculation were identified. We also identified putative target genes of the identified miRNAs and verified in vivo cleavage of a subset of these targets by 5'-RACE analysis. Using conserved miRNAs as internal control, we estimated that our analysis identified ~50% of miRNAs in soybean roots. Conclusion Construction and analysis of a small RNA library led to the identification of 20 conserved and 35 novel miRNA families in soybean. The availability of complete and assembled genome sequence information will enable identification of many other miRNAs. The conserved miRNA loci and novel miRNAs identified in this study enable investigation of the role of miRNAs in rhizobial symbiosis.